2018
DOI: 10.3847/1538-4357/aaee6c
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Covering Fraction Distribution of Swift/BAT AGNs with X-Ray and Infrared Observations

Abstract: We present an analysis of a sample of 69 local obscured Swift/Burst Alert Telescope active galactic nuclei (AGNs) with X-ray spectra from NuSTAR and infrared (IR) spectral energy distributions from Herschel and WISE. We combine this X-ray and IR phenomenological modeling and find a significant correlation between reflected hard X-ray emission and IR AGN emission, with suggestive indications that this correlation may be stronger than the one between intrinsic hard X-ray and IR emissions. This relation between t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 122 publications
2
21
0
Order By: Relevance
“…The cloud covering factor given in Table 1 decreases as the Eddington ratio increases. The consequences of changing covering factors have been discussed by, among many others, Oh et al (2015), Lanz et al (2019) and Lusso et al (2013). The low Eddington ratio objects require covering factors around 50%, with the covering factor decreasing to ∼ 5% for the highest Eddington ratio case.…”
Section: Discussionmentioning
confidence: 99%
“…The cloud covering factor given in Table 1 decreases as the Eddington ratio increases. The consequences of changing covering factors have been discussed by, among many others, Oh et al (2015), Lanz et al (2019) and Lusso et al (2013). The low Eddington ratio objects require covering factors around 50%, with the covering factor decreasing to ∼ 5% for the highest Eddington ratio case.…”
Section: Discussionmentioning
confidence: 99%
“…10 Here τ burst is fixed to 25 Myr. package to calculate the Spearman's rank correlation (Isobe et al 1986;Lavalley et al 1992), and perform bootstrap analysis (1000 samples) to derive the confidence intervals of the Spearman correlation coefficient and the null hypothesis probability (Lanz et al 2019). The null hypothesis is that there is no monotonic relation between two parameters.…”
Section: Dust Versus Post-burst Agementioning
confidence: 99%
“…An alternative approach, recently pursued by Ananna et al (2019), considers a small number of fixed AGN spectral models, but modifies the HXLF in order to fit the X-ray survey data. While it is important that the measured HXLFs be continuously improved, the observed increase in f 2 (e.g., Liu et al 2017), the connection between N H and R (e.g., Lanz et al 2019), and the increasing evidence for fundamental physical connections between the AGN and its environment (e.g., Ricci et al 2017), all strongly suggest that the observed AGN X-ray SED will be functions of both redshift and luminosity that should be considered in future XRB synthesis models.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, these results imply that AGNs that are seen through moderate-to-heavy amounts of obscuration exist in fundamentally different environments than those observed through lower N H columns, and are therefore probing different AGN populations (Draper & Ballantyne 2010;Buchner et al 2015). The direct fitting of nearby Swift-BAT AGNs by Lanz et al (2019) also found that more obscured objects have larger R, although the analysis of Ricci et al (2017) gave the opposite conclusion which could be explained by modeling degeneracies (see Lanz et al 2019). The combination of an increasing f 2 with z and a correlation of R with N H provides a physical template for the redshift evolution in R that is needed to fit the NuSTAR number counts.…”
Section: Model Setupmentioning
confidence: 91%
See 1 more Smart Citation